Efisiensi Teknis dan Sumber Inefisiensi Teknis Pada Usahatani Bawang Merah di Kabupaten Kupang (Pendekatan Maximum Likelihood Estimation) - Nainggolan, Viona Febrina; Proklamita, Tri Luchi (Fakultas Pertanian, Universitas Timor, 2024)
Kupang Regency is one of the red onion producers in the East Nusa Tenggara Province. The red onion production in Kupang Regency from 2020 to 2022 experienced a yearly decline. The issue of decreasing productivity in red onion farming is related to the inefficiency in the use of production inputs. This research aims to analyze the level of technical efficiency and sources of technical inefficiency in red onion farming in Kupang Regency. The sampling technique was done purposively, with a sample size of 64 farmers from three villages: Tarus Village, Uiboa Village, and Uitiutuan Village. Snowball sampling was used for sample selection. The analysis method employed was the stochastic frontier Cobb-Douglas production function, estimated using Maximum Likelihood Estimation (MLE). The research results indicate that the average level of technical efficiency achieved by red onion farmers in the research locations is 0.7864, or an average technical efficiency value of 78.64%. Sources of technical inefficiency in red onion farming include income, age, education, farming experience, family size, planting distance, and farmer groups. Positive influences on inefficiency are income, age, planting distance, and farmer groups, while education, farming experience, and family size have negative influences on red onion farming efficiency.